Archaeology of Medieval villages currently inhabited in Europe (OXFORD : ARCHAEOPRESS, 2019)
Archaeological interventions in European rural settlements have largely focussed on villages abandoned during the last millennium. Most hamlets and villages of medieval origin remain inhabited, however, and excavations have been scarce. This book details excavations of inhabited sites in the UK, the Netherlands, France, Scandinavia and Spain.
The Archaeology of Currently Inhabited Villages in Spain: The Case of AsturiasMargarita Fernández Mier; Jesús Fernández Fernández; Conclusion; Chris Wickham
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Archaeology, Medieval; Cities and towns, Medieval -- Europe; Cities and towns, Medieval; Archéologie médiévale.; Villes médiévales.; SOCIAL SCIENCE -- Archaeology; Archaeology, Medieval; Cities and towns, Medieval; Europe